Performance of Nitrogen and Phosphorus Removal of Moving Bed Biofilm Reactor Operated as Sequencing Batch - Tunc, Muslun Sara (CNR Çevre [EN], 2017)
In this study, nitrogen and phosphorus removal from municipal wastewater in moving bed biofilm reactor operated as sequencing batch was investigated. Kaldnes (K1) material as biofilm carrier media was used in the study. Operation consisted of anaerobic/aerobic/anoxic/aerobic phases with hydraulic residence times of 120 min/330 min/210 min/50 min. In the moving bed biofilm reactor with the filling ratio of 50% operated as sequencing batch, average effluent chemical oxygen demand (COD), ammonium-nitrogen (NH4-N), nitrite-nitrogen (NO2-N), nitrate-nitrogen (NO3-N) and phosphate-phosphorus (PO4-P) values after the cycle duration of 12 h were determined to be 27 mg/L, 0.7 mg/L, 0.04 mg/L, 0.6 mg/L and 0.7 mg/L, respectively. The average COD, NH4-N and PO4-P removal efficiencies were obtained as 92%, 97.5% and 91.3%, respectively.
Keywords: Engineering; Mühendislik